PENGEMBANGAN BLOG SUPPORT PEMBELAJARAN MATEMATIKA SEKOLAH MENENGAH ATAS - Arifin, Sujinal; Zulkardi; Darmawijoyo (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2010)
This study aims to (1) get a valid and practice prototype mathematics’ blog support for learning in senior high school, (2) see the effect of blog support for learning mathematics. That is used in this study is a developmental research that consist of conception, designing, collecting materials, assembling, trying out and distributing. Mathematics’ blog support was tried out to eleventh grade of senior high school student in SMA YPI Tunas Bangsa. The instruments for collecting data are test, observation, questioner, and document analyzing. Test is used to see students’ achievement. Observation is used to see students’ activities. Questioner is used to see students’ opinion after using mathematics’ blog support. Document analyzing is used to see opinions of expert review about validity and practically of mathematics’ blog support. The results of analysis are: (1) mathematics’ blog support which is developed has been valid and practice. Valid is based on expert review. Practice is based on one to one and small group. (2) Mathematics’ blog support which is developed has been effectivefor students’ activities and students’ achievement. DOI: 10.22342/jpm.4.2.817